Sosialisasi Penggunaan Aplikasi Google Classroom dan Google Meet kepada Guru SD Negeri 89 Pekanbaru - Diah Anugrah Dipuja; Fitra Alideai; Al Hafiza Mayritz Zahra; Denisa Nur Aulia; Nufal Al Hamid; Desri Annisa Ramadhani; Zahrah Fadhilah; Hurunia Hurunia; Hafizah Syahrani; Indri Latifa; Waldi Benerly Tua Sagala (Journal of Community Engagement Research for Sustainability, 2022)
The Covid-19 pandemic has had an impact on the world of education. The government has made several policies to prevent the transmission of Covid-19, including the face-to-face learning process being changed to bold learning. This makes educators and students at various levels, from universities to elementary schools, adapt to the learning process to remain effective and efficient. However, some elementary schools use a pick-up and drop-off system to school, this is because some teachers do not use bold learning applications and students' different economic levels to meet learning needs (mobile/laptop). The purpose of implementing community service, especially for teachers, is to equip teachers to have an understanding of the use of bold learning applications. The method used in this service activity is lecture and direct practice, presenting material for brave learning applications based on google classroom and google meet for SD Negeri 89 Pekanbaru teachers. The results obtained are that teachers understand how to use bold learning applications so that learning can run effectively even in the midst of the Covid-19 pandemic.